---------------------------
        Theorem[KECA-TLCA'2013]
      ---------------------------

  N. Kraus, M. Escardó, T. Coquand, and T. Altenkirch.
  Generalizations of Hedberg’s theorem.  In Typed Lambda Calculi and
  Applications, volume 7941 of Lecture Notes in Computer Science,
  pages 173-188.  Springer Berlin Heidelberg, 2013.

\begin{code}

module KECA where

open import Preliminaries

\end{code}

Some definitions and lemmas

\begin{code}

constant : {A B : Set}  (A  B)  Set
constant f =  x y  f x  f y

infix  30 _⁻¹
infixr 25 _•_

_⁻¹ : {A : Set} {x y : A}
     x  y  y  x
_⁻¹ = sym

_•_ : {A : Set} {x y z : A}
     x  y  y  z  x  z
_•_ = trans

infix  1 finally
infixr 0 _≡⟨_⟩_

_≡⟨_⟩_ : {A : Set} (x : A) {y z : A}  x  y  y  z  x  z
_ ≡⟨ p  q = p  q

finally : {A : Set} (x y : A)  x  y  x  y
finally _ _ p = p

syntax finally x y p = x ≡⟨ p ⟩∎ y ∎

sym-is-inverse : {X : Set} {x y : X} (p : x  y)
                refl  p ⁻¹  p
sym-is-inverse refl = refl

ap-id-is-id : {X : Set} {x y : X} (p : x  y)
             ap  z  z) p  p
ap-id-is-id refl = refl

refl-is-left-id : {X : Set} {x y : X} (p : x  y)
                 p  refl  p
refl-is-left-id refl = refl

refl-is-right-id : {X : Set} {x y : X} (p : x  y)
                  p  p  refl
refl-is-right-id refl = refl

sym-trans : {X : Set} {x y z : X} (p : x  y) (q : y  z)
           (q ⁻¹)  (p ⁻¹)  (p  q)⁻¹
sym-trans refl refl = refl

sym-sym-trivial : {X : Set} {x y : X} (p : x  y)
                 p  (p ⁻¹)⁻¹
sym-sym-trivial refl = refl

trans-assoc : {X : Set} {x y z w : X} (p : x  y) (q : y  z) (r : z  w)
             (p  q)  r  p  (q  r)
trans-assoc refl refl refl = refl

Kraus-Lemma₀ : {X Y : Set} (f : X  Y) (cf : constant f) {x y : X} (p : x  y)
              ap f p  (cf x x) ⁻¹  (cf x y) 
Kraus-Lemma₀ f cf {x} refl = sym-is-inverse (cf x x)

Kraus-Lemma₁ : {X Y : Set} (f : X  Y)  constant f  {x : X} (p : x  x)
              ap f p  refl
Kraus-Lemma₁ f cf {x} p = (Kraus-Lemma₀ f cf p)  (sym-is-inverse (cf x x)) ⁻¹

transport-paths-along-paths : {X Y : Set} {x y : X} (p : x  y) (h k : X  Y) (q : h x  k x) 
                            transport  z  h z  k z) p q  (ap h p) ⁻¹  q  (ap k p)
transport-paths-along-paths {X} {Y} {x} {.x} refl h k q = claim₀  claim₁
 where
  claim₀ : q  q  refl
  claim₀ = refl-is-right-id q
  claim₁ : q  refl  refl  q  refl
  claim₁ = refl-is-left-id (q  refl)

transport-paths-along-paths' : {X : Set} {x : X} (p : x  x) (f : X  X) (q : x  f x) 
                              transport  z  z  f z) p q  p ⁻¹  q  (ap f p)
transport-paths-along-paths' {X} {x} p f q = claim₀  claim₁
 where
  claim₀ : transport  z  z  f z) p q  (ap  z  z) p) ⁻¹  q  (ap f p)
  claim₀ = transport-paths-along-paths p  z  z) f q
  claim₁ : (ap  z  z) p) ⁻¹  q  (ap f p)  p ⁻¹  q  (ap f p)
  claim₁ = ap  pr  pr ⁻¹  q  (ap f p)) (ap-id-is-id p)

\end{code}

The main lemma and the theorem

\begin{code}

fix : {X : Set}  (X  X)  Set
fix f = Σ \x  x  f x

Kraus-Lemma : {X : Set} (f : X  X)  constant f  isProp (fix f)
Kraus-Lemma {X} f g (x , p) (y , q) =
  -- p : x ≡ f x
  -- q : y ≡ f y
  (x , p)        ≡⟨ pair⁼ r refl 
  (y , p')       ≡⟨ pair⁼ s t ⟩∎           
  (y , q) 
    where
     r : x  y
     r = x ≡⟨ p 
       f x ≡⟨ g x y 
       f y ≡⟨ q ⁻¹ ⟩∎
         y 
     p' : y  f y
     p' = transport  z  z  f z) r p
     s : y  y
     s = y   ≡⟨ p' 
         f y ≡⟨ q ⁻¹ ⟩∎
         y   
     q' : y  f y
     q' = transport  z  z  f z) s p'
     t : q'  q
     t = q'                         ≡⟨ transport-paths-along-paths' s f p' 
         s ⁻¹  (p'  ap f s)       ≡⟨ ap  pr  s ⁻¹  (p'  pr)) (Kraus-Lemma₁ f g s) 
         s ⁻¹  (p'  refl)         ≡⟨ ap  pr  s ⁻¹  pr) ((refl-is-right-id p')⁻¹)  
         s ⁻¹  p'                  ≡⟨ refl  
         (p'  (q ⁻¹))⁻¹  p'       ≡⟨ ap  pr  pr  p') ((sym-trans p' (q ⁻¹))⁻¹)  
         ((q ⁻¹)⁻¹  (p' ⁻¹))  p'  ≡⟨ ap  pr  (pr  (p' ⁻¹))  p') ((sym-sym-trivial q)⁻¹) 
         (q  (p' ⁻¹))  p'         ≡⟨ trans-assoc q (p' ⁻¹) p'  
         q  ((p' ⁻¹)  p')         ≡⟨ ap  pr  q  pr) ((sym-is-inverse p')⁻¹) 
         q  refl                   ≡⟨ (refl-is-right-id q)⁻¹  ⟩∎
         q  


Theorem[KECA-TLCA'2013] : {A : Set} (f : A  A)  constant f   A   A
Theorem[KECA-TLCA'2013] {A} f cf x = pr₁ (hA2F x)
 where
  F : Set
  F = fix f
  hF : isProp F
  hF = Kraus-Lemma f cf
  A2F : A  F
  A2F a = f a , cf a (f a)
  hA2F :  A   F
  hA2F = ∥∥-elim hF A2F

\end{code}